Multi-Mode Face-to-Face and Telephone Approach to Data Collection in Health Surveys: A Scoping Review - Guerra, Paulo Henrique [UNESP]; Sposito, Letícia Aparecida Calderão; Umpierre, Daniel; Florindo, Alex Antonio (MDPI, 2024)
Background/Objectives: The present study aims to identify information from health research studies that have used a mixed-methods data collection approach, considering the combination of face-to-face and telephone interviews (referred to as the MMFT approach), specifically focusing on identifying themes, objectives, designs, populations involved, and implementation processes. Methods: A scoping review was developed, with systematic searches performed in March 2024 across five databases, namely, PubMed; SciELO; Scopus; Web of Science; as well as Google Scholar and reference lists. The inclusion criteria were defined under the following categories: “Participants” (observational epidemiological studies, with no restrictions as to where they were carried out, sampling techniques, or sample profiles); “Concept” (use of MMFT in data collection), and “Context” (studies carried out in the health area, with no restrictions on the theme/subject). The review process was carried out by three researchers who worked independently. Results: From the initial 1515 potential references, the synthesis of this review included data from seven original studies, highlighting cross-sectional designs, involvement of adults and/or elderly people without specific health conditions, variability between data collection strategies, and complementary use of online approaches. Conclusions: Based on the evidence generated, it is recommended that future studies assess aspects of the MMFT approach in terms of response rate, cost reduction, and increasing the speed of conducting health surveys.
Keywords: data collection; health surveys; interviews as topic; review; telephone